Effect of Colchicine on Myocardial Injury in Acute Myocardial Infarction. Issue 11 (23rd August 2021) - Mewton, Nathan; Roubille, François; Bresson, Didier; Prieur, Cyril; Bouleti, Claire; Bochaton, Thomas; Ivanes, Fabrice; Dubreuil, Olivier; Biere, Loïc; Hayek, Ahmad; Derimay, François; Akodad, Mariama; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Inflammation is a key factor of myocardial damage in reperfused ST-segment–elevation myocardial infarction. We hypothesized that colchicine, a potent anti-inflammatory agent, may reduce infarct size (IS) and left ventricular (LV) remodeling at the acute phase of ST-segment–elevation myocardial infarction. Methods: In this double-blind multicenter trial, we randomly assigned patients admitted for a first episode of ST-segment–elevation myocardial infarction referred for primary percutaneous coronary intervention to receive oral colchicine (2-mg loading dose followed by 0.5 mg twice a day) or matching placebo from admission to day 5. The primary efficacy outcome was IS determined by cardiac magnetic resonance imaging at 5 days. The relative LV end-diastolic volume change at 3 months and IS at 3 months assessed by cardiac magnetic resonance imaging were among the secondary outcomes. Results: We enrolled 192 patients, 101 in the colchicine group and 91 in the control group. At 5 days, the gadolinium enhancement–defined IS did not differ between the colchicine and placebo groups with a mean of 26 interquartile range (IQR) [16–44] versus 28.4 IQR [14–40] g of LV mass, respectively ( P =0.87). At 3 months follow-up, there was no significant difference in LV remodeling between the colchicine and placebo groups with a +2.4% (IQR, –8.3% to 11.1%) versus –1.1% (IQR, –8.0% to 9.9%) change in LV end-diastolic volume ( P =0.49). Infarct size at 3 months was also not significantly different between the colchicine and placebo groups (17 IQR [10–28] versus 18 IQR [10–27] g of LV mass, respectively; P =0.92). The incidence of gastrointestinal adverse events during the treatment period was greater with colchicine than with placebo (34% versus 11%, respectively; P =0.0002). Conclusions: In this randomized, placebo-controlled trial, oral administration of high-dose colchicine at the time of reperfusion and for 5 days did not reduce IS assessed by cardiac magnetic resonance imaging. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03156816.